Quantification and pharmacokinetics of crizotinib in rats by liquid chromatography–tandem mass spectrometry. (23rd November 2015) - Qiu, Feng; Gu, Yanan; Wang, Tingting; Gao, Yingying; Li, Xiao; Gao, Xiangyu; Cheng, Shan
Abstract: Crizotinib is a small molecule inhibitor of anaplastic lymphoma kinase (ALK) and can be used to treat ALK‐positive nonsmall‐cell lung cancer. A rapid and simple high‐performance liquid chromatography–tandem mass spectrometry (LC‐MS/MS) method was developed and validated for the quantification of crizotinib in rat plasma using a chemical synthetic compound buspirone as the internal standard (IS). The plasma samples were pretreated by a simple protein precipitation with methanol–acetonitrile (1:1, v/v). Chromatographic separation was successfully achieved on an Agilent Zorbax XDB C18 column (2.1 × 50 mm, 3.5 µm). The gradient elution system was composed of 0.1% formic acid aqueous solution and 0.1% formic acid in methanol solution. The flow rate was set at 0.50 mL/min. The multiple reaction monitoring was based on the transitions of m / z = 450.3 → 177.1 for crizotinib and 386.2 → 122.2 for buspirone (IS). The assay was successfully validated to demonstrate the selectivity, matrix effect, linearity, lower limit of quantification, accuracy, precision, recovery and stability according to the international guidelines. The lower limit of quantification was 1.00 ng/mL in 50 μL of rat plasma. This LC‐MS/MS assay was successfully applied to the quantification and pharmacokinetic study of crizotinib in rats after intravenous and oral administration of crizotinib. The oral absolute bioavailability of crizotinib in rats was 68.6 ± 9.63%. Copyright © 2015 John Wiley & Sons, Ltd.